2020
DOI: 10.32479/ijeep.9917
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Large-Scale Integration of Wind Energy in Albania

Abstract: Recently, the Albanian government has compiled national energy strategy with a special focus on promoting the use of renewable energy sources (RES) which identifies a target of 42% of the final energy consumption from RES by 2030. In this paper, analyses are conducted in order to investigate to which extent and way the absorption capacity of the power system from RES electricity can be improved. As an effective approach of implementing wind power, fostering the accommodation of renewable energy sources, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Two previous research study (Malka et al, 2020 found that the site with the most wind potential is the area over the hills. Strictly speaking, the direct use of measured wind speed data for wind resource calculations results in power estimates that are representative only for the actual position of the wind-measuring instruments.…”
Section: Site Backgroundmentioning
confidence: 95%
See 4 more Smart Citations
“…Two previous research study (Malka et al, 2020 found that the site with the most wind potential is the area over the hills. Strictly speaking, the direct use of measured wind speed data for wind resource calculations results in power estimates that are representative only for the actual position of the wind-measuring instruments.…”
Section: Site Backgroundmentioning
confidence: 95%
“…• Levelized Cost of Electricity (LCOE) in electricity production can be defined as the present value of the electricity price produced in c€/kWh, taking into account the economic life of the park and the costs incurred in construction, operation, maintenance, and for fuel. Along this line, the generation cost during construction and production periods can be given expression ( 6) (Malka et al, 2020;IRENA, 2018):…”
Section: Economics Of Wind Turbinesmentioning
confidence: 99%
See 3 more Smart Citations